Specific effects of individualized cognitive training in children with attention-deficit/hyperactivity disorder (ADHD): the role of pre-training cognitive impairment and individual training performance - Minder, Franziska; Brandeis, Daniel (Developmental neurorehabilitation, 2019)
Objective: We investigated the impact of the pre-training neuropsychological (NP) impairment and of the training progress on the NP and behavioural outcome after computerized cognitive training (CogT) in children with ADHD. Method: Thirty-one participants underwent individualized CogT (focussing on one or two cognitive domains: working memory, inhibition, attention) over 12 weeks. NP tests and behaviour ratings served as outcome measures. Results: After CogT, significant improvements emerged according to parents’ ratings, but only on very few NP test measures. Children with milder/no pre-training NP impairment showed larger improvements on behavioural ratings than more impaired children. A steeper training performance slope was related to better behavioural outcomes. Conclusion: We find partial support for specific effects of CogT, but the assumption that an individually tailored selection of training tasks would be particularly beneficial for children with ADHD with NP deficits was not confirmed. Trial registration number: NCT02358941.
Gesehen am 14.10.2019